Workshop on Pesticide Exposure Assessment Paradigm for Non-Apis Bees: Foundation and Summaries. Issue 1 (3rd December 2018) - Boyle, Natalie K; Pitts-Singer, Theresa L; Abbott, John; Alix, Anne; Cox-Foster, Diana L; Hinarejos, Silvia; Lehmann, David M; Morandin, Lora; O'Neill, Bridget; Raine, Nigel E; Singh, Rajwinder; Thompson, Helen M; et al.
Abstract: Current pesticide risk assessment practices use the honey bee, Apis mellifera L., as a surrogate to characterize the likelihood of chemical exposure of a candidate pesticide for all bee species. Bees make up a diverse insect group that provides critical pollination services to both managed and wild ecosystems. Accordingly, they display a diversity of behaviors and vary greatly in their lifestyles and phenologies, such as their timing of emergence, degree of sociality, and foraging and nesting behaviors. Some of these factors may lead to disparate or variable routes of exposure when compared to honey bees. For those that possess life histories that are distinct from A. mellifera, further risk assessments may be warranted. In January 2017, 40 bee researchers, representative of regulatory agencies, academia, and agrochemical industries, gathered to discuss the current state of science on pesticide exposure to non- Apis bees and to determine how well honey bee exposure estimates, implemented by different regulatory agencies, may be protective for non- Apis bees. Workshop participants determined that although current risk assessment procedures for honey bees are largely conservative, several routes of exposure are unique to non -Apis bees and warranted further investigation. In this forum article, we discuss these key routes of exposure relevant to non- Apis bees and identify important research gaps that can help inform future bee risk assessment decisions.